Identification and Testing of Antidermatophytic Oxaborole-6-Benzene Sulphonamide Derivative (OXBS) from Streptomyces atrovirens KM192347 Isolated from Soil - Seham Abdel-Shafi; Abdul-Ra; Taghreed N. Almanaa; Ahmed H. Moustafa; Tamer M. M. Saad; Abdel-Rahman Ghonemey; Immacolata Anacarso; Gamal Enan; Nashwa El-Gazzar (MDPI AG, 2020)
There is a need to continue research to find out other anti-dermatophytic agents to inhibit causal pathogenic skin diseases including many types of tinea. We undertook the production, purification, and identification of an anti-dermatophytic substance by Streptomyces atrovirens. Out of 103 streptomycete isolates tested, only 20 of them showed antidermatophytic activity with variable degrees against Trichophyton tonsurans CCASU 56400 (T. tonsurans), Microsporum canis CCASU 56402 (M. canis), and Trichophyton mentagrophytes CCASU 56404 (T. mentagrophytes). The most potent isolate, S10Q6, was identified based on the tests conducted that identified morphological and physiological characteristics and using 16S rRNA gene sequencing. The isolate was found to be closely correlated to previously described species Streptomyces atrovirens; it was designated Streptomyces atrovirens KM192347 (S. atrovirens). Maximum antifungal activity of the strain KM192347 was obtained in modified starch nitrate medium (MSNM) adjusted initially at pH 7.0 and incubated at 30 °C in shaken cultures (150 rpm) for seven days. The antifungal compound was purified by using two steps protocol including solvent extraction and column chromatography. The MIC of it was 20 µg/mL against the dermatophyte cultures tested. According to the data obtained from instrumental analysis and surveying the novel antibiotics database, the antidermatophytic substance produced by the strain KM192347 was characterized as an oxaborole-6-benzene sulphonamide derivative and designated oxaborole-6-benzene sulphonamide (OXBS) with the chemical formula C13H12 BNO4S. The crude OXBS didn't show any toxicity on living cells. Finally, the results obtained herein described another anti-dermatophytic substance named an OXBS derivative.